2018
DOI: 10.7717/peerj.5121
|View full text |Cite
|
Sign up to set email alerts
|

Volatile profiling in Rhus coriaria fruit (sumac) from three different geographical origins and upon roasting as analyzed via solid-phase microextraction

Abstract: Rhus coriaria (sumac) is a fruit grown worldwide for its culinary use as a flavoring agent and for its health benefits. Despite several studies on R. coriaria non-volatile metabolites, much less is recognized concerning volatile composition within that genus. In an effort to expand on flavor profile sumac and its food products, we report on volatile profiling from three accessions of different origins including Palestine, Jordan and Egypt in addition to its cold tea and post roasting via headspace solid-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Similar conclusions could be deduced from the study conducted by Farag et al. (2018) who reported volatile profiling of sumac from three accessions (Palestine, Jordan and Egypt) and the different post‐roasting volatile products using headspace‐SPME. Results indicated the presence of different classes of terpenes and their oxygenated derivatives and non‐terpenic compounds including furans, aldehydes and hydrocarbon derivatives.…”
Section: Phytochemical Studiessupporting
confidence: 87%
See 1 more Smart Citation
“…Similar conclusions could be deduced from the study conducted by Farag et al. (2018) who reported volatile profiling of sumac from three accessions (Palestine, Jordan and Egypt) and the different post‐roasting volatile products using headspace‐SPME. Results indicated the presence of different classes of terpenes and their oxygenated derivatives and non‐terpenic compounds including furans, aldehydes and hydrocarbon derivatives.…”
Section: Phytochemical Studiessupporting
confidence: 87%
“…However, roasting the fruits from Palestine resulted in increasing the concentration of hazardous non‐terpenic furans and aldehydes derivatives especially furfural (34.37 %). It is worth noting that furans are known to occur in thermally processed food products, and the results of this particular investigation clearly indicated that the concentration of these carcinogenic compounds should be monitored carefully in roasted R. coriaria fruits, so concentrations are in line with the FDA guidelines and do not exceed 170 ng/g …”
Section: Phytochemical Studiesmentioning
confidence: 68%
“…At the industrial level, Sumac leaves and bark, which contain large amounts of tannins, were used for centuries in tanning fine leather [ 4 ]. In addition to its use as a culinary herb and tanning agent, Rhus coriaria has been used in Middle Eastern and South Asian countries, for thousands of years, as a traditional medicine for the treatment of several diseases including cancer [ 5 , 6 , 7 ]. Sumac fruits were used in folks medicine to treat several illnesses that include liver disease [ 8 ], diarrhea [ 8 , 9 , 10 ], urinary system issues [ 8 ], and ulcers [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In folk medicinal, it has been used for treating diarrhea [14]. Rhus coriaria consists of compounds such as tannins, phenolic acids, flavonoids, terpenoids, and essential oil composed of monoterpenes that have numerous biological activities, which are used as hair cleaning solutions or anti-dandruff agents for the improvement of dermatological problems [16,17]. It has antimicrobial, antiviral, antifungal, antioxidant, anti-inflammatory, and anticancer activities [18,19]; it is also used orally for reducing blood glucose, uric acid, and cholesterol levels [20][21][22].…”
Section: Introductionmentioning
confidence: 99%